Evaluation of the treatment program in the plan to develop the teaching of the Holy Koran in the general education stages of the city of Makkah - Alsulamie, Owaued Owied (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed at evaluating the therapeutic program in the plan to develop the teaching of the Holy Quran in the stages of general education in Mecca, and this related to variables: scientific qualification, years of experience and number of courses and specialization, and the study community shall be of all 19 teachers of the Qur’an subject enrolled in the program in Mecca(19) trainees in the second semester of the academic year 1442, The sample of the study consisted of all those enrolled in the program, the researcher used the descriptive method, and the researcher applied in the study questionnaire to collect information that helps extract the data of the authors and the number of questionnaire phrases (51) words after arbitration distributed in five axes (objectives of the training program, content of the training program, training methods, calendar tools and the environment accompanying the program), and the content analysis card for the program consisted of four axes (Program sources, program elements, program processes, and program standards) the number of card terms (71) words, and the collection test to measure the knowledge of the trainees of the program and consist of (15) questions of a multi-choice category containing four alternatives to each question, and to process the data statistically the researcher used the program statistical analysis SPSS. One of the most important findings reached by the researcher is the approval of the members of the sample of the study on the degree of meeting the therapeutic program in the plan to develop the teaching of the subject of the Holy Quran in the stages of general education in Mecca for the specific objectives, the approval of the members of the sample study on the degree of meeting the therapeutic program in the plan to develop the teaching of the subject of the Holy Quran in the stages of general education in The City of Mecca for the academic content. The study recommends the development of therapeutic plans for teachers of the Holy Quran subject according to the educational stages, with the continuation of the program and its development in order to achieve its goal.